Evidence and Human Genome Editing - Maschke, Karen J. (The Hastings Center report, 2018)
In July, the United Kingdom's Nuffield Council on Bioethics issued a report on human genome editing in which it said that editing a human embryo's genome to reduce the possibility that the future child will inherit a genetic disorder could be ethically acceptable when certain conditions are met: the intended use of genome-editing interventions secures and is consistent with the “welfare of the future person” and does not “increase disadvantage, discrimination or division in society.” Yet the Council noted that if current legal restrictions on the use of heritable genome-editing interventions were lifted, the interventions should be used only in the context of “well-designed and supervised studies” to ensure that they are safe and effective. Some people might contend that it is premature to talk about what kind of evidence—and how much—will be needed to gauge the safety and effectiveness of genome-editing interventions since the United Kingdom, the United States, and several other countries currently prohibit clinical trials that involve transferring into a woman an embryo whose genome was edited. Yet based on an analysis of evidentiary disputes involving several medical technologies (an analysis that I conducted with my Hastings colleague Michael Gusmano for a forthcoming book, Debating Modern Medical Technologies: The Politics of Safety, Effectiveness, and Patient Access), I suggest that now is the time to start the conversation about evidentiary standards for the use of genome editing in reproductive medicine.